The Potential of Binahong Leaves Extract Nanogel for Alveolar Bone Healing - Bernard, Bernard; Syafruddin Ilyas; Olivia Avriyanti Hanafiah (HM Publisher, 2024)
Alveolar bone defects pose a significant challenge in dental and oral health, requiring the exploration of novel therapeutic approaches for effective bone healing. The binahong (Anredera cordifolia) leaves are known for their rich bioactive compounds with diverse therapeutic properties, while nanogels, a drug delivery system, offer advantages such as controlled release and enhanced bioavailability. This review explores the potential of binahong leaf extract nanogel as a promising candidate for alveolar bone healing by discussing its preparation, characterization, and properties. Furthermore, it delves into the cellular and molecular mechanisms underlying alveolar bone healing. Based on our review, the effects of binahong leaves extract on bone cells and animal models indicate its therapeutic potential in alveolar bone healing by increasing the expression of growth factors and cells that are essential in bone healing. This review suggests that binahong leaves extract nanogel holds promise as a novel therapeutic intervention for alveolar bone healing. Further research and clinical studies are warranted to fully explore its potential.